Meningkatkan Hasil Belajar Pak Dengan Model PBL Berbantuan LKPD Fase C Kelas 5 SDN 102005 Durian Tinggung - Meyda Theresia Br Barus (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to determine the improvement of cognitive and affective learning outcomes in the dimensions of Faith, Devotion to God Almighty and Mutual Cooperation through the PBL model for students at SD Negeri 102005 Durian Tinggung. This type of research is classroom action research with research steps, namely planning, implementation, observation and reflection in each cycle. This study consists of two cycles. The research location is at SD Negeri 102005 Durian Tinggung. For grade V students with the material King David the Wise As. The time of the study was carried out in September 2024. The data collection technique used a learning outcome test and an affective observation rubric. The data analysis technique used a quantitative descriptive technique. From the results of the study, there was an increase in cognitive learning outcomes by 35% in the Proficient criteria and 45% in the Proficient criteria and 20% in the Eligible criteria. Affective Learning Outcomes using the PBL learning model have been proven to improve the affective learning outcomes of students at SD Negeri 102005 Durian Tinggung on the material King David the Wise. The results of the improvement can be seen from the number of students in cycle I, 100% of whom entered the Proficient criteria and in cycle II there was a significant change, namely 100% entered the Proficient criteria.